Optimization of diamond-like carbon thin film on copper substrate for carbon nanotubes synthesis by ACVD technique - Suttichart C. (2017)
© 2017 Trans Tech Publications, Switzerland. In this research, demonstrate plasma treatment on copper substrate by Radio Frequency Plasma (RF) using a mixture of 70%C 2 H 2 + 30%H 2 as the working gases. The plasma exposure time were varied from 10, 20 and 30 min under the electrical power of 50 Watts for synthesizing the diamond-like carbon (DLC) thin film on copper substrate. Thereafter, the substrates were used for synthesizing the carbon nanotubes (CNTs) via alcohol chemical vapor deposition technique (ACVD). It could be found that the plasma treatment for 10 min exhibited the small contact angle less than those of substrates treated with 20, 30 min and untreated sample which relate to the hydrophilic and affect to improve the adhesion and distribution of catalyst on substrate. The roughness of DLC film showed the different high and low level like hillock. After that, the 10 min treatment time sample was used for synthesizing the CNTs and the results found that the obtained CNTs showed good distribution on substrate.